Book Review: Young People Making it Work: Continuity and Change in Rural Places - Rayna Sage (Journal of Research in Rural Education, 2013)
In Young People Making it Work, Hernán Cuervo and Johanna Wyn use data from the Youth Research Centre's longitudinal Life Patterns study to follow Australian rural young adults over the span of two decades, giving voice to those coming of age during a period of rapid economic and social change. During the last half of the 20th century, changes in technology and regulations resulted in massive labor market reductions in the production-based industries that had previously provided economic stability for much of rural Australia. These changes, coupled with expansions in postsecondary education opportunities and new demands for educated workers in knowledge- and science-based fields, created new obstacles for rural young adults in the 1990s and into the early 2000s. In their challenge to urbancentric social research on education and work transitions and deficit approaches to understanding rural experiences, these authors highlight the expected and unexpected efforts rural individuals make to stay connected to the people and places they value most.